(3GdJfbjM GdQGFY aj TQM eNJUQ GdTQGFYs - (3GdSjhQj, GdMdj, GdCSOj, GdebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826(3g`s ((3Ydj CUZQ Hf dWa Gddg GdbRhjfjs)
(3ChdgG (B:s
(3GdMeO ddg GdYdj GdYXje(B...(3CeG HYO aEf Yde Gdabg dG jNai HdhZg GdZGjI TQaG(B...s
(3BNQgG (B:s
(3jcaj jejf GdebQ dg Cfg dG jYde GdJgeI dG CfgG djSJ MGUdI aj faS GdCeQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B906s
(3GdPQjYI(B:(3L(B4(3,U(B336(3,Qbe (B2059s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis